2017
DOI: 10.1158/1078-0432.ccr-15-2301
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Clinical Trial and Independent Patient-Derived Xenograft Study of Combined Targeted Treatment with Dacomitinib and Figitumumab in Advanced Solid Tumors

Abstract: Purpose: This phase I, open-label, single-arm trial assessed the safety and tolerability of dacomitinib-figitumumab combination therapy in patients with advanced solid tumors.Experimental Design: A standard 3 þ 3 dose escalation/deescalation design was utilized. Starting doses were figitumumab 20 mg/kg administered intravenously once every 3 weeks and dacomitinib 30 mg administered orally once daily. We also performed an independent study of the combination in patient-derived xenograft (avatar mouse) models of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Likewise, a phase II randomized second-line study of linsitinib vs. topotecan in relapsed SCLC failed to show any clinical activity, with a PFS that significantly favored topotecan [87], see Table 3. Figitumumab, another monoclonal antibody associated with IGF-1R, failed to show efficacy in NSCLC [177,178] but clinical data for SCLC is rare [174]. A placebo-controlled study of platinum and etoposide plus figitumumab in SCLC was halted due to low accrual and discontinuation of further clinical investigation of figitumumab after enrolment of n = 9 patients (NCT00977561).…”
Section: Targeted Therapies In Sclc Treatmentmentioning
confidence: 99%
“…Likewise, a phase II randomized second-line study of linsitinib vs. topotecan in relapsed SCLC failed to show any clinical activity, with a PFS that significantly favored topotecan [87], see Table 3. Figitumumab, another monoclonal antibody associated with IGF-1R, failed to show efficacy in NSCLC [177,178] but clinical data for SCLC is rare [174]. A placebo-controlled study of platinum and etoposide plus figitumumab in SCLC was halted due to low accrual and discontinuation of further clinical investigation of figitumumab after enrolment of n = 9 patients (NCT00977561).…”
Section: Targeted Therapies In Sclc Treatmentmentioning
confidence: 99%
“…Dacomitinib also exhibited potent anticancer activity in many cancer types in vitro [ 16 18 ]. In addition, the combination of dacomitinib with other targeted therapies have been reported to overcome acquired or de novo resistance to cancer chemotherapy [ 19 ]. In this paper, we evaluated the effect of dacomitinib on the reversal of ABCG2-mediated MDR.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary data on the efficacy of this treatment showed that 3 out of 61 (4.9%) patients had PR as the best overall response (BOR), and 22 (36%) had SD as BOR. The three patients with the PR had ovarian carcinoma, adenoid cystic carcinoma, and salivary gland carcinoma, while 8 of the 22 patients with SD had NSCLC [43].…”
Section: Other Combinations and Cancersmentioning
confidence: 99%